Combined Effect of Chemical Surface Treatment of Kevlar Fabric and PTFE Fillers on the Water-Involved Tribological Performance of Kevlar Fabric/Phenolic Laminate. Issue 2 (3rd March 2016) - Wang, Jianzhang; Liu, Ning; Yang, Jie; Han, Gaofeng; Yan, Fengyuan
ABSTRACT: The combined effect of chemical surface treatment of Kevlar fabric and solid lubricant polytetrafluoroethylene (PTFE) fillers on the water-involved tribological performance of Kevlar fabric/phenolic resin laminate was investigated. Results showed that the interfacial adhesion between Kevlar fabric and resin was improved because of chemical surface treatment on the Kevlar fabric, leading to a decreased wear rate but an increased friction coefficient of the laminate. The addition of PTFE fillers not only enhanced the wear resistance of the laminate but reduced its friction coefficient. Furthermore, the combination of surface treatment on Kevlar fabric and the PTFE filling can improve the wear resistance and friction-reducing property of the laminate to the largest extent.